An Ecological Approach towards Classification of Coastal Vegetation of India.- 1. Strand Vegetation - Ananda Rao, T.; Sastry, A. R. K. (Indian Forester, 1972)
The ecology of the Indian coastal vegetation which is not only of great theoretical but also of practical interest has hitherto been insufficiently known. Champion and Seth (1968) dealt this vegetation type in a concise manner under the group, ’Littoral and Tidal swamp forests of India’. During the last 12 years, extensive data have been collected on the physiographic, floristic and edaphic aspects, and based on these, an attempt is now made to analyse and to reclassify the Indian coastal vegetation in greater detail, but adhering to the original frame work given by Champion and Seth 1968. In the present paper, the coastal vegetation type has heen further sub-divided into three types: Sand strand, Rock strand and Coral strand. Under each type, the salient features such as distribution, topography, floriotics and edaphic characters pertinent to each type have been discussed at length with suitable summary diagrams based on relative cover value of plants from quadrats and the analytical data.